The incidence of anterior pituitary hormone deficiencies in patients with microprolactinoma and idiopathic hyperprolactinaemia. (19th June 2017) - Behan, L.A.; Moyles, P.; Cuesta, M.; Rogers, B.; Crowley, R.K.; Ryan, J.; Brennan, P.; Smith, D.; Tormey, W.; Sherlock, M.; Thompson, C.J.
Summary: Introduction: Patients with microprolactinoma and idiopathic hyperprolactinaemia are not generally considered to be at risk of hypopituitarism and are therefore not routinely screened for this abnormality. In our clinical practice, we have observed a number of patients with nonmacroadenomatous hyperprolactinaemia to have anterior pituitary hormone deficits. Aims: We aimed to establish the frequency and clinical significance of anterior pituitary hormone deficiencies, comparing patients with radiologically proven microprolactinomas and patients with idiopathic hyperprolactinaemia. Study Design: We retrospectively examined the casenotes of 206 patients with hyperprolactinaemia from our centre. Patients who did not fit the profile of surgically naïve microprolactinoma or idiopathic hyperprolactinaemia or who had incomplete data were excluded, resulting in a study group of 56 patients. Results: A total of 35 patients with MRI evidence of microprolactinoma were identified, three (8.57%) of whom had one or more anterior pituitary hormone deficiencies. A total of 21 patients with MRI‐negative idiopathic hyperprolactinaemia were identified, nine (42%) of whom had one or more anterior pituitary hormone deficiencies ( P <.01). Only one patient in the MRI‐positive group had deficiency that required hormone replacement, in contrast six patients in the MRI‐negative group had deficiencies that were of clinical significance and which required hormone replacement. Summary: This study shows a clinically significant incidence of anterior pituitary hormone deficiency in patients with idiopathic hyperprolactinaemia. The authors recommend that dynamic pituitary assessment should be considered routinely in this patient group. A prospective study would be required to assess the underlying cause for these abnormalities, as they suggest a nontumour pan‐pituitary process.